PECULIARITIES OF THE LENTIL PRODUCTIVITY FORMATION UNDER THE USE OF NITROGEN-FIXING AND PHOSPHATE-MOBILIZING MICROORGANISMS - Prysiazhniuk O.I.,; Slobodianiuk S.V.,; Topchii O.V.,; Sukhova H.I.,; Karpuk L.M.,; Kryvenko А.I.,; Svystunova I.V.,; Pavlichenko A.A., (Scientific Journal of Pedagogy and Economics, 2020)
To study the peculiarities of lentil productivity formation under the effect of nitrogen-fixing and phosphate-mobilizing microorganisms in the Forest-Steppe of Ukraine. Methods. Field, laboratory, and statistical. Results. The maximum number and weight of active nodules on the lentil roots were formed in the stage of bean filling when the plant's need for nitrogen was the highest. Seed inoculation with formulation Rizohumin contributed to a 5.3 times increase in the number of active nodules in the budding stage, 4.5 times in the flowering stage, and 3.8 times in the bean-filling stage compared to the control treatment. The best indicators of active symbiotic potential demonstrated the treatment with seed inoculation with Rizohumin and the use of phosphate-mobilizing formulation Polymixobacterin and Azohran B in combination with foliar dressing using Alga 600. In the same treatments, in the flowering stage, the maximum content of leghemoglobin in the fresh mass of nodules (5.58 and 5.50 mg/g) was obtained. In the flowering stage, plants formed the maximum leaf area (40 300 m2 /ha) in the treatments with Rizohumin, Azogran B, and Alga 600. When using a combination of Rizohumin, Polymixobacterin and Alga 600, 128.0 kg/ha of nitrogen, 43.4 kg/ha of phosphorus, and 60.8 kg/ha of potassium was needed for yield formation. At the same time, under the joint application of Rizohumin, Azorgan B and Alga 600, the need was 118.0 kg/ha, 40.0 kg/ha, and 56.0 kg/ha, respectively, which corresponded to the maximum indicators of the nutrient uptake in the experiment. The use of Rizohumin + Azogran B + +Alga 600 resulted in the lentil yield of 1.79 t/ha; whereas in the treatments with Rizohumin + Polymixobacterin + +Alga 600, the maximum yield was obtained (1.95 t/ha).